On-Site Treatment of Exertional Heat Stroke. (April 2015) - Sloan, Brian K.; Kraft, Emily M.; Clark, Dave; Schmeissing, Scott W.; Byrne, Brian C.; Rusyniak, Daniel E.
Background: Exertional heat stroke is a devastating condition that can cause significant morbidity and mortality. Rapid cooling is the most effective means of treating heat stroke, but little is published on the safety and logistics of cooling patients on site at a major sporting event. Purpose: To describe an on-site exertional heat stroke treatment protocol and to compare the outcomes of patients treated on site to those transferred to hospitals. Study Design: Descriptive epidemiological study. Methods: Using race-day medical records and ambulance run sheets, patients who developed exertional heat stroke at the Indianapolis half-marathon from 2005 to 2012 were identified. Exertional heat stroke was defined as runners with a core temperature measured with a rectal thermometer greater than 102°F and altered mental status. Clinical information and patient outcomes were abstracted from the race medical tent and hospital charts by 3 separate trained reviewers using structured methods and a data collection form. Two reviewers, using a RedCAP database and dual-data entry, abstracted records for each patient. A third arbitrated all discrepancies between reviewers. Clinical signs, treatments, and outcomes were calculated using descriptive statistics, and data were grouped and compared for patients treated on site or transferred to local hospitals for treatment. Results: Over 235, 000 athletes participated in the event over the 8-year period, with 696 seeking medical care. A total of 32 heat stroke victims were identified during the study period; of these, 22 were treated on site. Of these, 68% were treated with cold-water immersion and 59% were discharged home from the race. Ten exertional heat stroke patients were transported from the race course to local hospitals. None of them underwent cold-water immersion, and 40% of them were subsequently discharged home. No patients in the study died. Conclusion: On-site treatment of athletes who develop exertional heat stroke appears to be both safe and effective. On-site treatment may decrease the local burden of critically ill patients to emergency departments during large athletic events.